IMPACT OF ANTIBIOTIC RESISTANCE ON HEALTHCARE OUTCOMES - Imran Aslam; Ayesha Ashraf (Research Focus International Scientific Journal, 2024)
Antibiotic resistance (ABR) has arisen as a critical concern in contemporary healthcare, significantly impacting patient outcomes, healthcare systems, and worldwide public health. As bacteria develop resistance to widely utilized antibiotics, infections become progressively challenging to manage, leading to prolonged hospitalizations, elevated treatment expenses, and heightened morbidity and fatality rates. This study examines the effects of ABR on healthcare outcomes, encompassing clinical, economic, and systemic difficulties it poses. The paper emphasizes the significance of antimicrobial stewardship programs in alleviating these consequences and offers recommendations for improving existing hospital policies and procedures.